HUBUNGAN AKTIVITAS FISIK TERHADAP KEJADIAN OSTEOPOROSIS PADA LANSIA DI DESA TANJUNG KURUNG ILIR KABUPATEN LAHAT - Hili Aulianah; Nuriza Agustina (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2021)
Increasing life expectancy today has consequences with the emergence of various health problems in the elderly. One of the diseases commonly experienced by the elderly is Osteoporosis. In the village Tanjung Kurung Ilir, the elderly suffer from bone deformities. This study aims to determine the relationship of physical activity to the incidence of osteoporosis in the elderly 2020. The population in this study was all elderly, totaling 39 people. The sample of this study is the whole total population. This study uses a "Cross-Sectional" design. Statistical analysis using the Chi-Square test with p <= 0.05, this study on December 2020. The results obtained were 25 elderly (64.1%) who did the moderate physical activity, 20 elderly (51, 3%) elderly who have osteoporosis, there is a relationship between physical activity and the incidence of osteoporosis in the elderly with p-value = 0.000. The results of the study concluded that there was a relationship between physical activity and the incidence of osteoporosis in the elderly in the village Tanjung Kurung Ilir, Lahat district in 2020, obtained p-value = 0.000. It is hoped that this research can improve the quality of health services for the Tanjung Tebat Community Health Center in providing counseling for the community in increasing understanding and information about osteoporosis, especially regarding elderly exercise.Â Keywords:Â Physical Activity, Elderly, Osteoporosis